OFR-87-95 Recovery Of Heavy Metals With A Mixed Microbial Ecosystem - J. Bender (The National Institute for Occupational Safety and Health (NIOSH), 1996)
The objective of this research was to (1) Further develop cyanobacteria mats' for metal-tolerance and cold-tolerance, (2) test them for durability in the field environment and (3) assess them for metal sequestering potential with actual and simulated field samples. Results show that mats performed well In the field and effectively sequestered metals from actual and simulated field samples. Metal uptake from Iron Mountain Hine samples was for Ins 87%, Cu and Cd 99%, Initial concentrations (mg/L) were Zn = 3,250, Cu , 279, Cd = 28. In solutions simulating the Gulf Tunnel drainage, Zn and Mn were effectively removed by mats immobilized on glass wool. Effluent water, after treatment, generally had a Ph of 7 .5-8.5. Al though the final metal concentrations in the mats 'harvested from the decontaminated water were only 1% or less, the actual mechanism of metal deposit was probably a mat-mediated alteration of the environmental conditions causing the metals to deposit outside the mat as oxides or carbonates. Bioflocculents, released by the mats, were likely involved in the metal-removal process.